Introduction of a Strategic Board Game that is Aimed at Educating Children About Sustainable Development Goals of United Nations - Ozenc, Sirin Guney (European Journal of Social Science Education and Research, 2022)
The paper I want to share at this Education Conference is not the result of a research, but it is a product of a 26-year long education career. With all my observations during these 26 years, I found that especially high school students’ global awareness is low and developing a better awareness has become the forefront of my education phylosophy, so I create a syllabus and developed a strategic board game. I am a generation X teacher who tries to raise the generation Z kids and construct an education system for the Generation Alpha. On the other hand,Y-generation, my young colleagues that I am working with are also very different from me, but still ,we are sharing the same planet that needs our immediate care and awareness. The main goal of this syllabus is teaching the UN Sustainable Development Goals, so that they can internalize the goals to take actions. This paper contains the basic chapter explanations of the curriculum and the rulee of the strategic board game ECOTOPIA. In short , this curriculum and strategic board game is the product my educational experience and I would like to get support/opinion from my colleagues by presenting them in this conference. The philosophy of the curriculum is rising Global Awareness meanwhile understanding the sustainable development goals (SDG). On the other hand, the game Ecotopia is just covering some development goals. The game focused on renewable energy sources and pollution. When a student starts playing the game he/she has learned the renewable energy sources, pollution sources and etc but by the end of the game he/she would have a solid idea about how other countries affect your nature, how do states make decisions to change their investments nature friendly like electric cars, how unexpeced disasters like earthquake effec the country,how global warming is increasing aoutomatically and as World citizenship you nedd to take some actions to reduce it. Participants in the game need to develop various strategies regarding ecological conditions, sustainable energy sources, as well as attitudes towards air, water, and soil pollution. The goal of every player is to create a healthy and sustainable state.